Weak gravity conjecture in ModMax black holes: weak cosmic censorship and photon sphere analysis - Gashti, Saeed Noori; Afshar, Mohammad Ali S.; Alipour, Mohammad Reza; Sakalli, Izzet; Pourhassan, Behnam; Sadeghi, Jafar (Springer, 2025)
It seems that the regime of Hawking radiation and evaporation ultimately drives charged black holes toward super-extremality of the charge parameter and the dominance of extremal conditions. This progression, in turn, lays the groundwork for satisfying the necessary conditions for the Weak Gravity Conjecture (WGC). Preliminary studies indicate that black holes such as the Reissner-Nordstr & ouml;m (RN) model, in their initial form, lack the capacity to sustain super-extremality of the charge parameter. If such conditions arise, these black holes transition into naked singularities - a scenario that is highly undesirable due to the loss of causality and the breakdown of space-time geometry. This raises whether the inability to sustain super-extremality is an inherent property of the model or a consequence of the approximations and precision limitations employed in its construction. To address this, we turned to the ModMax model, which represents an extension of the RN model. Our analysis revealed that the ModMax model not only accommodates super-extremality of the charge parameter but also, under certain conditions, emerges as a promising candidate for investigating the WGC. Furthermore, we independently observed how the inclusion of the de Sitter radius (& ell;\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\ell $$\end{document}) in the AdS model and F(R) gravitational corrections - both of which enhance and complicate the model - can have a direct impact on the range of super-extremal charge tolerance which, in turn, provides the realization of the conditions necessary for the WGC.